Costs and Gains of Circular Labour Migration: The Case of Ukerewe and Muleba Districts, Tanzania (Tanzania Journal for Population studies and Development, 2021)
Circular labour migration has both costs and gains. Surprisingly, in most cases the costs are ignored while assessing the gains from migration, hence resulting into over-exaggeration of the potentials of migration. This study was conducted in Kakukuru and Nyakabango wards of Ukerewe and Muleba districts, respectively, with the aim of assessing the costs and gains of circular labour migration. Data was collected using household surveys, focus group discussions and key informant interviews. Qualitative and quantitative methods were used in data analysis. A total of 512 households sampled randomly were involved in the study. The findings revealed that the costs and gains from circular labour migration displayed almost a similar pattern across the studied localities. Both costs incurred and gains received were considerably small. The gains received by households by involving in circular labour migration were higher than the cost of circular labour migration, but the difference between the two was small. It is recommended that the government, at all levels, should strengthen this undertaking so that gains from circular labour migration can be maximized. Policy makers should think of vitalizing circular labour migration through enacting laws, as well as including circular labour migration in large national surveys such as the National Population and Housing Census, as well as the Household Demographic Survey, so as to track its contribution to the household as well as to the nation at large.